Walaiku Homestay - Gintik, Dana Merlize; Simon, Kelly; Minik @ Sylvester, Sylvia Ahmui; Lukas, Joss; Poumin, Tatiana Natasha (2016)
We intend to start a homestay called "Walaiku". Our homestay is a cultural theme homestay.where we highlight the three major ethnics in Sabah that are kadazandusun, rungus and murut. We want to make a homestay that can give a new experience to our customers and able them to learn the culture that have in Sabah. Such as, traditional food, traditional custom, the lifestyle, souvenirs and so on. We choose to run a homestay because this kind of business nowadays is popular, especially for tourists who come to visit our country. We also want to give the best service to our customers in satisfying their needs and wants so that to keep them feel comfortable in our homestay. This company's market potential are it will be well- known in Sabah because this type of business is very popular nowadays, so our homestay can stay long in this business industry. The business venture will start on 1 September 2019 and we intend to employ people to fill the following positions in our company.